MENYINGKAP KEARIFAN LOKAL BALI UNTUK MODUL DAN EFEKTIVITASNYA TERHADAP PENINGKATAN LITERASI KEBENCANAAN SISWA PADA PEMBELAJARAN IPS SMAN 1 GIANYAR - I Wayan Sumartika; I Putu Sriartha; I Made Pageh (STKIP Singkawang, 2025)
This study aims at developing Social Studies module based on Balinese local wisdom that is valid, practical and effective in enhancing disaster literacy among the students at senior high school level. The research employs Research and Development (R&D) approach, using 3D model involving define, design and develop, modified from Sivasailam Thiagarajan. The data were collected through observation, interview, document analysis, content validity, module practicality assessment and disaster literacy instruments that measure students’ cognitive, affective and psycomotor. The validity test result indicates that the module's content, media, and language validity are classified as very good. The practicality test results show that the module is highly practical. The effectiveness test results indicate that: (1) The normalized N-gain calculation for the control class was indicating a decline, while the experimental class categorized as moderate. (2) The N-gain score of the experimental class exceeds that of the control class, proving that the developed module is effective in improving disaster literacy. (3) The module also had a impact on students’ disaster literacy. Based on the research findings, it can be concluded that (1) the module is based on Balinese local wisdom, (2) the modul has been validated as highly reliable (3) the modul has been assessed as practical by both teachers as well as students. (4) the module is effective in enhancing students’ disaster literacy. Based on the research finding, it is recommended that the teachers and students utilize this module as a contextual learning resource to foster independent learning environment based on local wisdom.